Calreticulin Expression in Human Carcinomas: A Systematic Review and Meta-Analysis - Palacon, Mariana Paravani [UNESP]; Ferrisse, Tulio Morandin [UNESP]; de Oliveira Barbeiro, Camila [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Bufalino, Andreia [UNESP] (EpiSmart Science Vector, 2023)
Objective: The present study performed a systematic review and meta-analysis of observational studies on whether calreticulin levels could represent a prognostic factor in carcinoma patients. Calreticulin (CRT) is a multifunctional protein in the endoplasmic reticulum that can play distinct roles in different cancers. Methods: The search was performed in PubMed, Scopus, the Cochrane Library, Web of Science, Lilacs, Science Direct, Embase, Bireme, and SciELO databases. After a full-text evaluation, only 14 articles remained. The RoBANS tool assessed the risk of bias. The metaanalysis was performed with R software, and the odds ratio (OR) was the effect measure. The random effects model was chosen, and the quality of evidence was evaluated according to GRADE. Result: The most frequent carcinomas were in the breasts and the colon. CRT expression varied according to carcinoma origin and type, but these diseases had a prevalence of high CRT levels, indicating tumor progression. The high CRT levels were associated with lymph node metastasis (OR = 3.06 [1.71; 5.48]/p = 0.0002/I2 = 0%). All included articles had a blinding bias. Conclusion: High CRT levels may represent a prognostic factor for metastatic lymph nodes in carcinoma patients.
Keywords: Calreticulin; carcinoma; neoplasms; prognosis; systematic review